Notes from the People’s Circle for Palestine - Jenna Maingot (Radical Teacher)
The People’s Circle for Palestine at the University of Toronto (UofT) was a complex and messy place with opportunities for learning, community building, and enacting a more just world. This piece explores the encampment from a student perspective. I offer personal reflections, learnings, and questions that arose from my experiences as an encampment participant